Traditional and new forms of organisation and representation in the platform economy. (1st December 2018) - Karolien Lenaerts; Zachary Kilhoffer; Mehtap Akgüç
Abstract : This article investigates whether the existing frameworks of industrial relations and social dialogue can also be applied to work in the platform economy. It further questions what role the traditional Social Partners can play in dealing with the challenges of this new form of work. The article maps new forms of organisation, of both workers and platforms, and explores how these interact with the traditional actors and structures. While organising platform workers is difficult, numerous successful efforts to do so exist, including by grassroots organisations, worker cooperatives and formal unions. All of these, to different degrees, perform similar functions to those of traditional Social Partners.